2015
DOI: 10.5812/ircmj.22451v2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Successful Aging of Iranian Old Adult Women

Abstract: Background:Aging is an irreversible natural process characterized by a decline in both the physical and mental status of individuals. Because of multiple factors, this process and its consequences vary greatly between individuals. A successful aging (SA) is the target of current health policies and well-being of individuals. Knowing the factors that contribute to SA and its barriers would translate in measurements that increase the quality of life of elderly and reduce health costs.Objectives:The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Iran is estimated to face a sudden increase in the elderly population between 2030 and 2040. As a result, after experiencing epidemiological changes in diseases, Iran must prepare itself for managing the elderly wave in the upcoming decades [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iran is estimated to face a sudden increase in the elderly population between 2030 and 2040. As a result, after experiencing epidemiological changes in diseases, Iran must prepare itself for managing the elderly wave in the upcoming decades [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…They should also focus on a purposeful life based on ideal, meaningful goals and incentives, be in close contact with others, and improve their sense of self-esteem [ 8 ]. That is why, in recent years, we have seen a rise in various terms such as successful aging, active aging, healthy aging, positive aging, productive aging, and proper elderly [ 4 , 6 , 8 , 9 ], which provoke a good and positive life in the aging period. Each of these concepts represents a different approach to the benefits and potentials of aging [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that aging and its implications vary greatly between elderly Iranian women and men. Previous studies indicated that Iranian women follow different strategies to achieve optimal health due to which they are more likely to experience healthy aging in a natural way [15]. Furthermore, it has also been observed that they perceive optimal mental health through physical health.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have greater longevity. Studies suggest that the personality characteristics, unique perspectives, and lifestyles of women may contribute to their health status, high flexibility, and successful aging (Javadi Pashaki, Mohammadi, Jafaraghaee, & Mehrdad, 2015 ; Sheffler, 2011 ). Women can be considered good subjects to understand strategies for SA.…”
mentioning
confidence: 99%